Persistent Mullerian Duct Syndrome with Transverse Testicular Ectopia: Rare Presentation of Inguinal Hernia - Gupta, Ashish; Panda, Nilanjan; Saha, Makhan Lal; Ganguly, Shuvro; Bandyopadhyay, Samik Kumar; Das, Ruchira (Urology Journal, 2013)